(untitled) (Eurasian Journal of Ecology, 2024)
Defective interfering viruses and particles (DIVs/DIPs) are viral mutants that arise during viral replication, exerting significant effects on viral pathogenesis and host immune responses. These entities have garnered increasing interest due to their potential therapeutic and biotechnological applications. This study aims to explore the multifaceted roles of DIVs/DIPs in modern medicine and biotechnology, focusing on their ability to modulate viral infections and act as antiviral agents. The purpose of this research is to examine how DIVs/DIPs can be harnessed for therapeutic interventions, particularly in antiviral therapy and immune modulation. Key directions include investigating their capacity to interfere with viral replication, reduce viral loads, and enhance host immune defenses. The study also explores the biotechnological applications of DIVs/DIPs, including their role in vaccine development and the design of novel antiviral drugs. Methodologically, information was gathered from a diverse range of reliable sources, including references from NCBI, PMD, and other trusted academic databases. These resources were carefully analyzed to explore the potential applications of defective interfering viruses and particles (DIVs/DIPs) in modern medicine and biotechnology. The collected data provided a comprehensive overview of the mechanisms by which DIVs/DIPs interfere with viral replication and modulate immune responses. This approach ensured that the exploration of the topic was grounded in well-established scientific literature and recent advancements in the field. The results highlight the potential of DIVs/DIPs to suppress viral replication, indicating their utility as a therapeutic tool in combating viral infections. The analysis concludes that DIVs/DIPs represent a promising area of research with significant implications for the development of novel antiviral therapies. This study contributes to the growing body of knowledge on viral interference and opens new avenues for biotechnological innovations. The practical significance lies in the potential application of DIVs/DIPs in both therapeutic settings and in the advancement of biotechnological tools Keywords: defective interfering viruses (DIVs), viral interference particles, antiviral therapy, viral replication interference, immune modulation, biotechnological applications, vaccine development